L’éloignement de la Famille : Repartir à Zéro Vers le Vide (2015)
The family is a very perceptible element in the novels Disgrace J.M Coetzee (2008),The trial Franz Kafka (1983), The Human Stain Philip Roth (2000) and Mon coeur àl’étroit Marie Ndiaye (2007). This article aims to analyze the unstable relation between thecharacters and their families. In this regard, a comparative literary analysis is proposedin order to present an alternative reading of this novels. This analysis focuses on threeelements mainly: the detachment phenomenon and the characters’ differentpoints of view, the debts transmission as a fatal a condemnation, and finally thecharacters’ silent suffering as a resistance and fate symptom.